2008
DOI: 10.1523/jneurosci.5424-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Saccade Target Selection in the Superior Colliculus: A Signal Detection Theory Approach

Abstract: How the brain selects one action from among multiple options is unknown. A main tenet of signal detection theory (SDT) is that sensory stimuli are represented as noisy information channels. Therefore, the accuracy of selection might be predicted by how well neuronal activity representing alternatives can be distinguished. Here, we apply an SDT framework to a motor system by recording from superior colliculus (SC) neurons during performance of a color, oddball selection task. We recorded from sets of four neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
104
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 85 publications
19
104
1
Order By: Relevance
“…Previous recording studies have identified neural correlates of target selection for saccadic and pursuit eye movements in the SC (7,(11)(12)(13)(14)(15)(16)(17). Furthermore, inactivation and microstimulation studies have demonstrated that manipulations of SC activity can actually change the eye movement choices made by animals, establishing that the SC plays a causal role in target selection for eye movements (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous recording studies have identified neural correlates of target selection for saccadic and pursuit eye movements in the SC (7,(11)(12)(13)(14)(15)(16)(17). Furthermore, inactivation and microstimulation studies have demonstrated that manipulations of SC activity can actually change the eye movement choices made by animals, establishing that the SC plays a causal role in target selection for eye movements (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, activity related to eye-movement target selection has been identified in the superior colliculus (SC) (7,(11)(12)(13)(14)(15)(16)(17), frontal eye field (18)(19)(20), lateral intraparietal area (10,(21)(22)(23), and supplementary eye fields (24), all areas in which signals related to eye movement execution are seen and in which electrical microstimulation and/or temporary inactivation affects the execution of eye movements (25)(26)(27)(28)(29)(30)(31). For reaching movements, target selection activity has been observed in the dorsal premotor area (32)(33)(34), a region from which reaches can be electrically elicited (35), as well as in the parietal reach region (36,37), which exhibits reach-related planning and execution signals (38,39).…”
mentioning
confidence: 99%
“…Second, in visuomotor experiments, visual stimuli were well separable, both at the retina, and in early sensory responses of neurons within the visuomotor pathways. This holds also for example for the midbrain superior colliculus (SC), a crucial sensorimotor interface for the programming and generation of eyehead orienting responses (Arai et al, 2004;Kim and Basso, 2008). The actual visual response selection leading to either averaging or bimodal responses is therefore attributable to neural processing, rather than to visual peripheral limitations.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Competition between different populations, combined with local-excitatory/global-inhibitory interactions, shapes the population that represents the saccade goal. Task constraints and stimulus saliency help favor neurons that represent the target to win this competition, yet also averaging may be the result of this competition (van Opstal and Van Gisbergen, 1990;Glimcher and Sparks, 1993;Arai et al, 2004;Kim and Basso, 2008).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation